Avaliação do potencial fisiológico de sementes de girassol (Helianthus annuus L.) - Oliveira, Fabrícia Nascimento de (Universidade Federal Rural do Semi-Árido, 2011)
The evaluation of the physiological potential of seeds is an essential element of programs control for seed quality. The germination test, conducted under laboratory conditions, usually, overestimates the physiological potential of seed lots, therefore, increasing the need for improvement tests towards the evaluation of seed vigour. Thus, this study pursues to evaluate the physiological quality of sunflower seeds, Multissol and Catissol cultivars, each one represented by five lots. Firstly, the quality of seed lots was determined by germination test, first count, seedling emergency under greenhouse conditions and emergence rate index, besides the determination of water content of seeds. The evaluation of the physiological potential was carried out through accelerated aging tests, traditional methods and saturated NaCl solution (for 24, 48 and 72 hours at 42°C), controlled deterioration (seed moisture content of 20%, 22% and 24% at 42°C, for 72 hours) and electrical conductivity (25 or 50 seeds, imbibed in 50mL and 75mL at 25°C and 30°C, of 6, 12, 18 and 24 hours). The delineating used in this stage was completely randomized in a factorial arrangement with four replications for each cultivar and test conducted separatedly. From the obtained results, it was concluded that the accelerated aging tests with saline solution at 42°C/24h and electrical conductivity using the combination (25°C/75mL/50 seeds) were clear enough for the evaluation of the physiological potential of sunflower seeds. The tests of controlled deterioration and accelerated aging traditional procedure did not result to be an efficient choice for detecting the differences among lots of sunflower seeds, however, additional studies are necessary to determine more appropriate procedures for their performance.
Evaluate of physiological potential of seeds of sunflower (Helianthus annuus L.)
Keywords: Helianthus annuus L.; Sementes; Germinação; Helianthus annuus L.; Seeds; Germination; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA